Interrogating the Effectiveness of Nigeria’s Counterterrorism Efforts and the Variation in Boko Haram Terrorism Trajectory - OWOJORI, Abimbola Joseph; FASUAN, Emmanuel Olawale; ILORI, Oladapo Mayowa; MATANMI, Kareem A. (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2021)
This paper examines the effectiveness of Nigeria’s counterterrorism efforts since 2009 from the perspective of the variation in Boko Haram sect’s trajectory and organisational capability. Given that the goal of counterterrorism is degradation of terrorists’ operational capabilities and circumvention of their armed hostilities, this study argues that Nigeria’s counterterrorism techniques, measures and campaigns have not been effective to the extent that the Boko Haram sect has remained resilient. By examining the group’s operational capacity, organisational basing, political ties, and myriads of armed hostilities, the study concludes that Nigeria’s counterterrorism approaches and efforts need to be holistic and more strategic to achieve desirable counterterrorism outcomes.